Educational Planning Adequacy as Undergraduate Teaching Tool in a Learning-oriented Education Model - Ascencio Peralta, Claudia (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2016)
Educational planning involves the organization of a set of ideas and activities that develop an educational process with meaning, significance and continuity. It is a model or pattern that can deal in an orderly and consistent way, with situations that students will face in their professional or everyday life and in the case of the teacher, with his or her teaching practice. The Universidad Latinoamericana (ULA) did not have a standardized educational planning format, so that formats used by teachers in different school years were analyzed, until a proposal that combined components of syllabi and lesson plans in a modern and appropriate format were produced, one adapted to the educational model of this institution. The analysis of the formats and educational planning from some teachers allowed to determine the required adjustments to the format, the responsible for filling some sections as well as to make suggestions for additional resources required by teachers to provide quality teaching.